2017
DOI: 10.1186/s12872-017-0660-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of risk factors affecting the in-hospital prognosis of patients with acute ST segment elevation myocardial infarction after percutaneous coronary intervention

Abstract: BackgroundTo determine the factors affecting the in-hospital prognosis of patients with acute ST segment elevation myocardial infarction (STEMI) after percutaneous coronary intervention (PCI), and to establish its prognostic discriminant model.MethodsA total of 701 consecutive STEMI patients undergoing PCI were enrolled in this study. The patients were divided into two groups, good prognosis and poor prognosis, based on whether the patient had adverse outcomes (death or heart function ≥ grade III) at discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 70 publications
2
10
0
Order By: Relevance
“…A similar relationship was found for diabetes [24,25]. This relationship could be explained mainly due to the pathogenesis of atherosclerosis and higher frequency of MVD in patients with kidney failure and diabetes compared to those without kidney function impairment [24,25].…”
Section: Acs -Acute Coronary Syndrome Ami -Acute Myocardial Infarctisupporting
confidence: 71%
See 1 more Smart Citation
“…A similar relationship was found for diabetes [24,25]. This relationship could be explained mainly due to the pathogenesis of atherosclerosis and higher frequency of MVD in patients with kidney failure and diabetes compared to those without kidney function impairment [24,25].…”
Section: Acs -Acute Coronary Syndrome Ami -Acute Myocardial Infarctisupporting
confidence: 71%
“…Previously published studies revealed that elevated creatinine level was associated with poor myocardial blood flow and with an increased risk of death during the one-year follow-up after emergency PCI procedures in patients with STEMI [23]. A similar relationship was found for diabetes [24,25]. This relationship could be explained mainly due to the pathogenesis of atherosclerosis and higher frequency of MVD in patients with kidney failure and diabetes compared to those without kidney function impairment [24,25].…”
Section: Acs -Acute Coronary Syndrome Ami -Acute Myocardial Infarctimentioning
confidence: 62%
“…waist/hip ratio, dietary patterns, apolipoproteins, psychosocial factors) have been found in recent years. 29 The effect of self-management intervention on these factors was not examined in our study. Future studies to examine the effects of the intervention on these risk factors are needed.…”
Section: Variablesmentioning
confidence: 84%
“…STEMI has high morbidity and mortality. Risk stratification is of extreme importance for better patient outcome [14]. Our goal was to test some of the previously reported predictors of mortality in STEMI patients in an Egyptian cohort.…”
Section: Discussionmentioning
confidence: 99%